Uji Daya Hambat Asap Cair Sabut Pinang terhadap Pertumbuhan Bakteri Bacillus cereus dan Pseudomonas aeruginosa - Iryani .; Suryelita .; Dwi Kurnia Putri (Jurnal Periodic Jurusan Kimia UNP, 2013)
This research was to study about influence of increasing consentrations of areca catechu’s liquid smoke for inhibit phatogenic and food spoilage bacteria activities by using paper disc method. Variation concentration of areca catechu’s liquid smoke was use 10, 15, 20, 25, 35, 50, 75  and 100%(v/v) to inhibit Bacillus cereus and Pseudomonas aeruginosa. Result of this research showed maximum inhibition of areca catechu’s liquid smoke is at 100% concentration with inhibit diameter 18,3mm for Bacillus cereus and 16 mm for Pseudomonas aeruginosa. GC-MS identified important components in areca catechu’s liquid smoke as bacteria activities inhibitor are phenol derivate and acetic acid.